56 Comparison of morbidity, mortality and cost impact of stage B and stage C heart failure underline the clinical and economic need for national heart failure prevention strategy. (7th October 2015) - James, S; Waterhouse, D; Murphy, T; Kenny, C; Wilkinson, M; O'Connell, E; Gallagher, J; Watson, C; O'Hanlon, R; Ledwidge, M; McDonald, K
Abstract : Introduction: Heart failure (HF) has hit the epidemic proportion and is incurring significant cost to the health care system. Given the major morbidity, mortality and economic burden of this condition, a prevention strategy needs careful assessment to determine its role in the future health care policy. The STOP-HF project has underlined the clinical and cost effectiveness of a biomarker driven risk stratification and intervention strategy in those at risk for HF. Supportive data to establish the widespread application of this strategy would come from a comparative analysis of patients at risk for HF and those of a new community diagnosis of HF followed in a disease management programme. To assess the importance of HF prevention, we report the morbidity, mortality and economic costs of an at-risk cohort compared to established community HF. Method: 1566 patients attending the HF prevention unit and rapid access clinic for possible new onset HF from 2002 up to end of 2012 were selected for this analysis. Using Doppler echocardiography, patients were categorised to stage A (risk factors for HF with no structural or functional impairment of the heart), stage B (asymptomatic LV systolic dysfunction [B-LVSD], or isolated LV diastolic dysfunction [B-LVDD]), and stage C (symptomatic HF with reduce LVEF [C-REF] or preserved LVEF [C-PEF]). Follow-up time for events was until the end of 2014. Hospitalisations were collected, confirmed by HIPE records and categorised as HF event, other cardiovascular (other-CV) event, non-cardiovascular (non-CV) event and death. In the pre-specified cost analysis, direct costs associated with emergency hospitalisations were analysed using a case-mix approach from the perspective of the healthcare provider. Result: 1097 patients were in stage A, 173 stage B (112 B-LVDD and 61 B-LVSD), and 296 stage C (181 C-PEF and 115 C-REF). BNP increased through the stages at 19.1 pg/mL, 62.8 pg/mL, 67 pg/mL, 185 pg/mL and 384.5 pg/mL. Figure 1 showed that the HF events and death rate increased across the spectrum. The other-CV events are higher in B-LVDD group compare to the B-LVSD group. C-REF has more other-CV events compared to C-PEF, but the non-CV events are similar. In the costing sub-study of 1, 025 patients for whom detailed costing data were available, emergency CV hospitalisation costs per patient per annum were €313 ± 1222, €350 ± 1095 and €899 ± 1228 for stages A to C respectively. The data also show that emergency non-CV hospitalisation costs per patient per annum were €422 ± 1078, €560 ± 1316 and €2739 ± 4769 for stages A to C respectively, underlining a dramatic 4-fold increase emergency hospitalisation costs between stage B and C. Conclusion: The clinical and costs impact of HF care escalate significantly with the development of the symptomatic phase of HF syndrome. These data along with the positive clinical and cost effectiveness analysis of the STOP-HF data underline the need for national activation of the STOP-HF strategy.